A Sustainable Transportation System Model: The Case of Jakarta (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2015)
Jakarta, the capital city of Indonesia, is the fastest growing region with 6.5% economic growth in 2012. This condition leads to an increased demand of various goods and services, one of which is a reliable transport system. Jakarta's transport demand growth can be seen from trend in the number of motor vehicles. Number of vehicle increased from 7,967,489 in 2006 to 11,997,519 in 2010, with an increase in the number of motorcycles (65%) and passenger cars (51%). Active vehicle operated in DKI Jakarta that has been dominated by private vehicle is causing vehicle activity growth exceeds available road capacity, which is vital for keeping the environment well functioned. This research was conducted for analyzing relationship of economic growth and transportation system and its impact on environment particularly road capacity and emission; achieved by building transportation system model using system dynamics. Based on result of research, it is concluded that Jakarta’s current system transportation is not sustained which is indicated by road density and emission reached its environment capacity.